Epitaxial Lift-Off of Flexible GaN-Based HEMT Arrays with Performances Optimization by the Piezotronic Effect - Chen, Xin; Dong, Jianqi; He, Chenguang; He, Longfei; Chen, Zhitao; Li, Shuti; Zhang, Kang; Wang, Xingfu; Wang, Zhong Lin (Nano-Micro Letters, 2021)
High-electron-mobility transistors (HEMTs) are a promising device in the field of radio frequency and wireless communication. However, to unlock the full potential of HEMTs, the fabrication of large-size flexible HEMTs is required. Herein, a large-sized (> 2 cm2) of AlGaN/AlN/GaN heterostructure-based HEMTs were successfully stripped from sapphire substrate to a flexible polyethylene terephthalate substrate by an electrochemical lift-off technique. The piezotronic effect was then induced to optimize the electron transport performance by modulating/tuning the physical properties of two-dimensional electron gas (2DEG) and phonons. The saturation current of the flexible HEMT is enhanced by 3.15% under the 0.547% tensile condition, and the thermal degradation of the HEMT was also obviously suppressed under compressive straining. The corresponding electrical performance changes and energy diagrams systematically illustrate the intrinsic mechanism. This work not only provides in-depth understanding of the piezotronic effect in tuning 2DEG and phonon properties in GaN HEMTs, but also demonstrates a low-cost method to optimize its electronic and thermal properties. Highlights: 1 A large size (> 2 cm2) nitride membrane with High-electron-mobility transistor (HEMTs) arrays was successfully separated from sapphire substrate onto flexible substrate by an electrochemical lift-off technique. 2 Without adding extra cost, the piezotronic effect is utilized to optimize the electric transport and thermal conductivity properties of the HEMTs by modulating the physical properties of the 2DEG and phonons. 3 This study aims to open up a new way to fabricate high-performance GaN-based HEMTs and expand practical applications in flexible electronics.